The Right to be Forgotten in the Digital Age: A Comparative Analysis Between Spain and Peru - Arbildo Pérez, Natalia Ivett; Medina Rivas Plata, Anthony Rolando (Universidad Hemisferios, 2026)
The right to be forgotten has become one of the most relevant legal responses to the indefinite retention of personal information online. This article analyzes its content, limits, and conditions for its exercise from a comparative perspective between Spain and Peru. Methodologically, it combines a doctrinal review of open-access academic literature with a normative and jurisprudential analysis. The study argues that the right to be forgotten is not equivalent to erasing history or a general power of censorship, but rather a right to protect personal data aimed, above all, at limiting the disproportionate and targeted search of inaccurate, decontextualized, irrelevant, or excessive information. In Spain, the model has received explicit recognition and relatively stable criteria based on the GDPR, Organic Law 3/2018, and the Costeja case law. In Peru, although Law 29733 does not explicitly address it, the current framework has evolved through administrative regulations, constitutional jurisprudence, and the regulations approved by Supreme Decree 016-2024-JUS, which incorporates de-indexation. It is concluded that the Peruvian system still requires more precise legislative formulation and a more consistent balancing test against freedom of expression.